PENGARUH ARUS KAS OPERASI DAN PERTUMBUHAN PENJUALAN TERHADAP HARGA SAHAM PADA PERUSAHAAN INDEKS LQ45 YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN (2012-2016) - Kumayas, Natalia Debora; Pangemanan, Sifrid; Alexander, Stanly (Universitas Sam Ratulangi, 2018)
This research aims to examine the influence the effect of revenue and growth of the company on stock prices on LQ45 listed on Indonesia Stock Exchange 2012-2016. The population used in this study is the LQ45 company index listed on the Indonesia Stock Exchange 2012-2016. Method of sampling by purposive sampling according to predetermined criteria. The number of samples collected by 6 companies. Research data is secondary data obtained from Indonesia stock exchange (BEI) in 2012-2016. The collected data were analyzed using the first data analysis done by classical testing before hypothesis testing. Hypothesis testing in this research is multiple linear regression analysis with t test, f test, and coefficient of determination. The results of this study indicate that the variable cash flow positive and not significant to stock prices. This shows that the operation does not affect the high stock prices. While the growth of positive and significant sales to stock prices. This suggests that sales growth is driving high stock prices low.keywords: Operating cash flow, sales growth, stock price